A method for preparing graphene material based on template method
The template method uses copper sulfate crystal catalytic polymerization reactions to solve the problem of low graphite synthesis and high cost, and achieve efficient and low -cost graphite material preparation.
Patent Information
- Application Number
- CN202211674252.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-26
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-12-26
AI Technical Summary
In the prior art, the yield of synthetic graphyne is low and the cost is high, which limits the mass production and application of graphyne.
Graphite -based materials are prepared by the template -based method, and copper sulfate crystals are used as polymer templates and catalysts, and aggregate reactions are performed in an inert gas atmosphere to synthesize graphite pupa materials.
Increased the synthetic yield of graphite materials, while reducing the synthetic cost, which is more economical and efficient than traditional methods.
Smart Images

Figure CN116177541B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field related to the preparation of graphyne materials, and in particular to a method for preparing graphyne materials based on a template method. Background Art
[0002] Graphdiyne is composed of sp hybridized carbon atoms on the ethynyl unit and sp 2 A new type of carbon material composed of hybrid carbon atoms, its molecular structure is a two-dimensional planar network formed by conjugated diyne bonds connecting benzene rings. Graphyne molecules can be stacked to form a layered structure through van der Waals forces and π-π interactions. Therefore, Graphyne has high π binding, adjustable electronic properties, a two-dimensional planar structure and a uniformly distributed pore structure, showing unique photoelectrochemical and energy storage properties, and has great application potential in the fields of energy and catalysis.
[0003] Compared with traditional graphene, graphyne has a natural band gap energy, which allows graphyne to be directly used in the preparation of optoelectronic devices. At the same time, the electrical conductivity of graphyne is very close to that of silicon, and it is expected to be widely used in the fields of electronics and semiconductor research.
[0004] The existing methods for synthesizing graphyne have low yield and high cost, which greatly restricts the mass production of graphyne and limits its application areas. Summary of the invention
[0005] The present application provides a method for preparing graphyne material based on a template method, which improves the synthesis yield of graphyne material and reduces the synthesis cost of graphyne material.
[0006] The technical solution of this application is as follows:
[0007] According to a first aspect of an embodiment of the present application, a method for preparing a graphyne material based on a template method is provided, comprising:
[0008] (1) 8-13 g of anhydrous copper sulfate is completely dissolved in 15-30 ml of pure water at 80-100° C. to prepare a hot saturated copper sulfate solution;
[0009] (2) transferring the hot saturated solution of copper sulfate to a culture dish and allowing it to cool until small crystals are formed;
[0010] (3) transferring the small crystals to a saturated copper sulfate solution prepared by dissolving 1 to 3 g of anhydrous copper sulfate in 5 to 20 ml of pure water at 20 to 40° C. to obtain copper sulfate crystals suitable for the growth of graphyne;
[0011] (4) Synthesizing graphite monomers using hexabromobenzene as raw material through a series of chemical reactions;
[0012] (5) In an inert gas atmosphere, a plurality of copper sulfate crystals of a preset size and 10-20 ml of pyridine are added to a reaction container, and then 40-80 mg of graphite monomer is added to perform a polymerization reaction at 80-110° C. to obtain a graphyne material.
[0013] Optionally, the hot saturated copper sulfate solution is prepared by completely dissolving 11 g of anhydrous copper sulfate in 20 ml of pure water at 80°C.
[0014] Optionally, the saturated copper sulfate solution is prepared by completely dissolving 2.07 g of anhydrous copper sulfate in 10 ml of pure water at 20°C.
[0015] Optionally, in step (5), oxygen is removed by bubbling nitrogen into the reaction vessel to form an inert gas atmosphere.
[0016] Optionally, in step (5), the ratio of the number of copper sulfate crystals to the volume of pyridine and the weight of graphite monomer is 1:5:20.
[0017] Optionally, in step (5), 3 copper sulfate crystals of a preset size and 15 ml of pyridine are added to a reaction container, and then 60 mg of graphite monomer is added, and a polymerization reaction is carried out at 80-110° C. to obtain a graphyne material.
[0018] Beneficial effects:
[0019] The present application relates to a method for preparing a graphyne material based on a template method, comprising: completely dissolving 8 to 13 g of anhydrous copper sulfate in 15 to 30 ml of pure water at 80 to 100° C. to prepare a hot saturated solution of copper sulfate; transferring the hot saturated solution of copper sulfate to a culture dish and letting it stand and cool until small crystals are generated; transferring the small crystals to a saturated solution of copper sulfate prepared by dissolving 1 to 3 g of anhydrous copper sulfate in 5 to 20 ml of pure water at 20 to 40° C. to obtain copper sulfate crystals suitable for the growth of graphyne; synthesizing graphite monomers using hexabromobenzene as a raw material through a series of chemical reactions; in an inert gas atmosphere, adding a number of copper sulfate crystals of a preset size and 10 to 20 ml of pyridine to a reaction container, and then adding 40 to 80 mg of graphite monomers, and performing a polymerization reaction at 80-110° C. to obtain a graphyne material; by using copper sulfate crystals as a polymerization template and catalyst to prepare graphyne, the yield is improved while the cost is reduced compared with the traditional method.
[0020] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The drawings herein are incorporated into the specification and constitute a part of the specification, illustrate embodiments consistent with the present application, and together with the specification are used to explain the principles of the present application, and do not constitute an improper limitation on the present application.
[0022] Figure 1 is a schematic diagram of a process for preparing a graphyne material based on a template method according to an exemplary embodiment;
[0023] Figure 2 is a schematic diagram of a molecular structure of a graphite monomer according to an exemplary embodiment;
[0024] Figure 3 is a schematic diagram of the molecular structure of another graphite monomer according to an exemplary embodiment;
[0025] Figure 4 is a schematic diagram of the molecular structure of another graphite monomer according to an exemplary embodiment. DETAILED DESCRIPTION
[0026] In order to enable ordinary persons in the art to better understand the technical solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the accompanying drawings.
[0027] The following will be combined with the attached Figure 1 ~Attached Figure 4 A method for preparing graphyne material based on a template method according to an embodiment of the present invention is described in detail, wherein: Figure 1 A schematic diagram of the molecular structure change of a Graphyne material during the preparation of a Graphyne material in a method for preparing a Graphyne material based on a template method provided as an exemplary embodiment of the present application. Figure 1 As shown, the steps of a method for preparing a graphyne material based on a template method provided by an exemplary embodiment of the present application are as follows:
[0028] (1) 8-13 g of anhydrous copper sulfate is completely dissolved in 15-30 ml of pure water at 80-100° C. to prepare a hot saturated copper sulfate solution;
[0029] (2) transferring the hot saturated solution of copper sulfate to a culture dish and allowing it to cool until small crystals are formed;
[0030] (3) transferring the small crystals to a saturated copper sulfate solution prepared by dissolving 1 to 3 g of anhydrous copper sulfate in 5 to 20 ml of pure water at 20 to 40° C. to obtain copper sulfate crystals suitable for the growth of graphyne;
[0031] (4) Synthesizing graphite monomers using hexabromobenzene as raw material through a series of chemical reactions;
[0032] (5) In an inert gas atmosphere, a plurality of copper sulfate crystals of a preset size and 10-20 ml of pyridine are added to a reaction container, and then 40-80 mg of a graphite monomer is added, and a polymerization reaction is carried out at 80-110° C. to obtain a graphyne material, wherein preferably, nitrogen is bubbled into the reaction container to remove oxygen so as to form an inert gas atmosphere, and the ratio of the number of copper sulfate crystals to the volume of pyridine and the weight of the graphite monomer is 1:5:20.
[0033] The present application relates to a method for preparing a graphyne material based on a template method, comprising: completely dissolving 8 to 13 g of anhydrous copper sulfate in 15 to 30 ml of pure water at 80 to 100° C. to prepare a hot saturated solution of copper sulfate; transferring the hot saturated solution of copper sulfate to a culture dish and letting it stand and cool until small crystals are generated; transferring the small crystals to a saturated solution of copper sulfate prepared by dissolving 1 to 3 g of anhydrous copper sulfate in 5 to 20 ml of pure water at 20 to 40° C. to obtain copper sulfate crystals suitable for the growth of graphyne; synthesizing graphite monomers using hexabromobenzene as a raw material through a series of chemical reactions; in an inert gas atmosphere, adding a number of copper sulfate crystals of a preset size and 10 to 20 ml of pyridine to a reaction container, and then adding 40 to 80 mg of graphite monomers, and performing a polymerization reaction at 80-110° C. to obtain a graphyne material; by using copper sulfate crystals as a polymerization template and catalyst to prepare graphyne, the yield is improved while the cost is reduced compared with the traditional method.
[0034] Example 1
[0035] 11g of anhydrous copper sulfate is completely dissolved in 20ml of pure water at 80°C to prepare a hot saturated solution of copper sulfate; the hot saturated solution of copper sulfate is transferred to a culture dish and allowed to stand and cool until small crystals are generated; the small crystals are transferred to a saturated solution of copper sulfate prepared by dissolving 2.07g of anhydrous copper sulfate in 10ml of pure water at 20°C to obtain copper sulfate crystals suitable for the growth of graphyne; hexabromobenzene is used as a raw material to synthesize graphite monomers through a series of chemical reactions; under an inert gas atmosphere, 3 copper sulfate crystals of appropriate sizes and 15ml of pyridine are added to a reaction container, and then 60mg of graphite monomer is added, and a polymerization reaction is carried out at 80-110°C to obtain a graphyne material; compared with traditional methods, graphyne is prepared by using copper sulfate crystals as a polymerization template and catalyst, while the yield is increased and the cost is reduced.
[0036] Example 2
[0037] The present application relates to a method for preparing graphyne material based on a template method, comprising: completely dissolving 8g of anhydrous copper sulfate in 15ml of pure water at 80°C to prepare a hot saturated copper sulfate solution; transferring the hot saturated copper sulfate solution to a culture dish and letting it stand and cool until small crystals are generated; transferring the small crystals to a saturated copper sulfate solution prepared by dissolving 1g of anhydrous copper sulfate in 5ml of pure water at 20°C to obtain copper sulfate crystals suitable for the growth of graphyne; synthesizing graphite monomers using hexabromobenzene as a raw material through a series of chemical reactions, wherein the molecular structure of the graphite monomer is as follows Figure 2 As shown; in an inert gas atmosphere, several copper sulfate crystals of preset sizes and 10 ml of pyridine are added to a reaction container, and then 40 mg of graphite monomer is added, and a polymerization reaction is carried out at 80-110°C to obtain a graphyne material; by using copper sulfate crystals as a polymerization template and catalyst to prepare graphyne, the yield is improved while the cost is reduced compared to traditional methods.
[0038] Example 3
[0039] The present application relates to a method for preparing a graphyne material based on a template method, comprising: completely dissolving 13 g of anhydrous copper sulfate in 30 ml of pure water at 100° C. to prepare a hot saturated copper sulfate solution; transferring the hot saturated copper sulfate solution to a culture dish and allowing it to cool until small crystals are generated; transferring the small crystals to a saturated copper sulfate solution prepared by dissolving 3 g of anhydrous copper sulfate in 20 ml of pure water at 40° C. to obtain copper sulfate crystals suitable for the growth of graphyne; synthesizing a graphite monomer using 1,3,5-trifluorobenzene as a raw material through a series of chemical reactions, wherein the molecular structure of the graphite monomer is as follows: Figure 3 As shown; in an inert gas atmosphere, several copper sulfate crystals of preset sizes and 20 ml of pyridine are added to a reaction container, and then 80 mg of graphite monomer is added, and a polymerization reaction is carried out at 80-110°C to obtain a graphyne material; by using copper sulfate crystals as a polymerization template and catalyst to prepare graphyne, the yield is improved while the cost is reduced compared to traditional methods.
[0040] Example 4
[0041] The present application relates to a method for preparing a graphyne material based on a template method, comprising: completely dissolving 10 g of anhydrous copper sulfate in 25 ml of pure water at 100° C. to prepare a hot saturated copper sulfate solution; transferring the hot saturated copper sulfate solution to a culture dish and letting it stand and cool until small crystals are generated; transferring the small crystals to a saturated copper sulfate solution prepared by dissolving 2.5 g of anhydrous copper sulfate in 20 ml of pure water at 20° C. to obtain copper sulfate crystals suitable for the growth of graphyne; synthesizing a graphite monomer using 1,3,5-tribromobenzene as a raw material through a series of chemical reactions, wherein the molecular structure of the graphite monomer is as follows: Figure 4As shown; in an inert gas atmosphere, 4 copper sulfate crystals of a preset size and 20 ml of pyridine are added to a reaction container, and then 80 mg of graphite monomer is added, and a polymerization reaction is carried out at 80-110°C to obtain a graphyne material; by using copper sulfate crystals as a polymerization template and catalyst to prepare graphyne, the yield is improved while the cost is reduced compared to the traditional method.
[0042] Example 5
[0043] The present application relates to a method for preparing graphyne materials based on a template method, wherein 13g of anhydrous copper sulfate is dissolved in 15ml of pure water at 100°C to prepare a hot saturated solution, and the solution is transferred to a culture dish while hot and allowed to stand for cooling; small crystals precipitated from the hot saturated solution are transferred to a saturated copper sulfate solution at room temperature, and the precipitated copper sulfate crystals are collected after standing overnight; copper sulfate crystals are placed in a reaction vessel and pyridine is added to cover the copper sulfate crystals, and nitrogen is bubbled into the pyridine to remove oxygen; 60mg of monomer M1 is dissolved in 15ml of pyridine under an inert gas environment, and nitrogen is bubbled into the solution to remove oxygen. After 5 days of reaction, the copper sulfate crystals covered with graphyne are taken out, the crystals are dissolved in pure water, and the solids are collected by centrifugation, and the product is washed to obtain solid graphyne.
[0044] Although the preferred embodiments of the present application have been described, those skilled in the art may make additional changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications falling within the scope of the present application.
[0045] Obviously, those skilled in the art can make various changes and modifications to the present application without departing from the spirit and scope of the present application. Thus, if these modifications and variations of the present application fall within the scope of the claims of the present application and their equivalents, the present application is also intended to include these modifications and variations.
Claims
1. A method for preparing graphyne material based on template method, characterized in that: The method comprises: (1) 8-13 g of anhydrous copper sulfate is completely dissolved in 15-30 ml of pure water at 80-100° C. to prepare a hot saturated copper sulfate solution; (2) transferring the hot saturated solution of copper sulfate to a culture dish and allowing it to cool until small crystals are formed; (3) transferring the small crystals to a saturated copper sulfate solution prepared by dissolving 1 to 3 g of anhydrous copper sulfate in 5 to 20 ml of pure water at 20 to 40° C. to obtain copper sulfate crystals suitable for the growth of graphyne; (4) Synthesizing graphite monomers using hexabromobenzene as raw material through a series of chemical reactions; (5) In an inert gas atmosphere, a plurality of copper sulfate crystals of a preset size and 10-20 ml of pyridine are added to a reaction container, and then 40-80 mg of graphite monomer is added to perform a polymerization reaction at 80-110° C. to obtain a graphyne material.
2. The method according to claim 1, characterized in that The hot saturated copper sulfate solution is prepared by completely dissolving 11 g of anhydrous copper sulfate in 20 ml of pure water at 80°C.
3. The method according to claim 1, characterized in that The saturated copper sulfate solution is prepared by completely dissolving 2.07 g of anhydrous copper sulfate in 10 ml of pure water at 20°C.
4. The method according to claim 1, characterized in that: In step (5), oxygen is removed by bubbling nitrogen into the reaction vessel to form an inert gas atmosphere.
5. The method according to claim 1, characterized in that In step (5), the ratio of the amount of copper sulfate crystals to the volume of pyridine and the weight of graphite monomer is 1:5:
20.
6. The method according to claim 1, characterized in that In step (5), 3 copper sulfate crystals of a preset size and 15 ml of pyridine are added to a reaction container, followed by adding 60 mg of graphite monomer, and a polymerization reaction is carried out at 80-110° C. to obtain a graphyne material.
Citation Information
Patent Citations
Method for preparing graphite alkyne film
CN101774570A
Beta-graphdiyne and synthesis method and application thereof in field of energy storage
CN106865526A